Upper and lower bounds for the blow-up time of a fourth-order parabolic equation with exponential nonlinearity - Shuting Chang; Yaojun Ye (Electronic Research Archive)
This paper investigated the blow-up properties of solutions to the initial value problem for a fourth-order nonlinear parabolic equation with an exponential source term. By using an improved concavity method, we obtained upper and lower bound estimates for the blow-up time of the solution.